Optical Fibre Grating Refractometers for Resin Cure Monitoring. - Buggy, Stephen J.; Chehura, Edmon; James, Stephen W.; Tatam, Ralph P. (Institute of Physics (IOP), 2007)
The use of fibre grating refractometers as a means of monitoring the cure of a UVcured epoxy resin is presented. The wavelength shift of the attenuation bands of a long period grating and the spectral response of a tilted fibre Bragg grating sensor were measured simultaneously during the cure of the resin and compared with measurements made using a fibre optic Fresnel based refractometer. The results showed a good correlation (6 x 10 -3 rius) and illustrate the potential of the techniques for non-invasive composite material cure monitoring.
Keywords: optical fibre sensor; refractive index; cure monitoring; fibre gratings